HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG GANGGUAN JIWA TERHADAP SIKAP MEMBERIKAN PERTOLONGAN KESEHATAN JIWA - Dafli, Iswati Husna; Annis, Fathra; Karim, Darwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Mental disorders are disturbance in mental function, experienced by a person and have an impact on the process of living in the community. The wrong treatment due to the ignorance of people around sufferer causes disturbance in providing mental health care. This study aims to determine the relationship between the level of public knowledge about mental disorders toward provide mental health care. The research design used is descriptive correlation research design and cross-sectional approach. Research sample is 102 respondents by using total sampling technique. The measuring tool used is a questionnaire that has been tested for validity and reliability. The analysis used is univariate analysis to know the frequency distribution and bivariate analysis using chi-square test with error degree (α) 0,05. The result of this research shows that 56 (54,9%) respondents have enough knowledge and 57 respondents (55,9%) have negative attitude in giving mental health care. The statistical results show that there is a significant relationships between the level of public knowledge about mental disorders on the attitude of providing mental health care, with p value = 0,045. Based on the results of the study, the researchers recommend that the Puskesmas can provide promotive efforts or health counseling about mental health involving families and communities.Keywords: Attitude, knowledge, mental disorders, mental health help